2004
DOI: 10.1097/00126334-200406010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term CD4+ T-Cell Response to Highly Active Antiretroviral Therapy According to Baseline CD4+ T-Cell Count

Abstract: Current treatment guidelines for HIV infection recommend a relatively late initiation of highly active antiretroviral therapy (HAART). Nevertheless, there is still a concern that immune recovery may not be as complete once CD4+ T cells have decreased below a certain threshold. This study addressed the long-term response of CD4+ T-cell counts in patients on HAART and analyzed the influence of baseline CD4+ T-cell counts, baseline viral load, and age. An observational analysis of evolution of CD4+ T cells in 861… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
95
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 21 publications
22
95
2
2
Order By: Relevance
“…Other authors have not found an association between mortality and age. 19,44,54 We must recognize some limitations in our study. One of the limitations common to all cohort studies is that they may not be representative of all HIV-infected patients.…”
Section: Discussionmentioning
confidence: 94%
“…Other authors have not found an association between mortality and age. 19,44,54 We must recognize some limitations in our study. One of the limitations common to all cohort studies is that they may not be representative of all HIV-infected patients.…”
Section: Discussionmentioning
confidence: 94%
“…O achado foi superior ao encontrado por Souza Jr. et al 18 em uma amostra representativa nacional, em que 41% dos pacientes tinham indicação imediata da TARV na avaliação inicial. Da mesma forma, nossa proporção foi superior à descrita por autores internacionais, em que a proporção de início tardio da TARV variou de 36% a 60% 11,13,14,30,31 , mas foi semelhante à encontrada por Brook et al 12 (66%). Chama a atenção que 4,8% (n = 15) foram incluídos como início tardio da TARV pela definição clínica.…”
Section: Discussionunclassified
“…19 Patients initiating HAART experience substantial increases in CD4 cell counts regardless of the CD4 cell count at initiation, with slightly greater average increases in patients with low CD4 cell counts at initiation. [20][21][22] In the Swiss HIV Cohort Study 21,23 and a Spanish cohort, 24 the likelihood that patients achieved a CD4 count >500 cells/µL up to 5 years after starting HAART was inversely associated with baseline CD4 cell count, and in gay men enrolled in the Multicenter AIDS Cohort Study, the CD4 cell count increased during the first 2 years of therapy but reached a plateau thereafter. 25 Poorer outcomes in patients starting HAART at low CD4 cell counts, compared with those starting at higher CD4 cell counts, are therefore likely to be explained by the lower CD4 cell counts experienced by these patients after initiation of HAART.…”
Section: Discussionmentioning
confidence: 99%